Young at Heart: Combining Strategies to Rejuvenate Endogenous Mechanisms of Cardiac Repair - Maghin, Edoardo; Garbati, Patrizia; Quarto, Rodolfo; Piccoli, Martina; Bollini, Sveva (Frontiers in Bioengineering and Biotechnology, 2020)
True cardiac regeneration of the injured heart has been broadly described in lower vertebrates by active replacement of lost cardiomyocytes to functionally and structurally restore the myocardial tissue. On the contrary, the adult mammalian heart is endowed with an impaired reparative response following severe injury (i.e. myocardial infarction), and characterized by meagre wound healing program and detrimental remodelling, which can lead to cardiomyopathy and heart failure overtime. Lately, a growing body of preclinical and clinical efforts have focused on stem cell-based therapies for myocardial regeneration, with the working hypothesis that stem cells transplanted into the heart could give rise to new viable and functional cardiovascular cells to replenish the lost ones. Nevertheless, multiple independent evidences have demonstrated that injected stem cells are more likely to modulate the cardiac tissue via beneficial paracrine effects, which can enhance cardiac repair and reinstate the embryonic program and cell cycle activity of endogenous cardiac stromal cells and resident cardiomyocytes. Therefore, increasing interest has been addressed to the therapeutic profiling of the stem cell secretome (as the whole of cell-secreted soluble factors), with peculiar regard to the cardio-active potential of cell-released extracellular vesicles, including exosomes carrying cardioprotective and regenerative RNA molecules. In addition, the use of cardiac decellularized extracellular matrix has been recently suggested as promising biomaterial to develop novel therapeutic strategies for myocardial repair, as either source of molecular cues for regeneration, biological scaffold for cardiac tissue engineering or biomaterial platform for the functional release of factors. In this review, we will specifically discuss the biological and therapeutic relevance of these two approaches with ad hoc interest in their feasibility to rejuvenate endogenous mechanisms of cardiac repair up to functional regeneration.